The Effect Of Vitamin C On The Cerebral Cortex Neurons Of Rats Exposed By Prenatal Noise Stress - Luh Gde Evayanti (Global Publications, 2018)
The development of cerebral cortex neurons is important due to the complexity of synaptogenesis. Various stressors including prenatal noise exposure may have adverse effect on this process. Vitamin C has been reported to act as an antioxidant in the brain that could function as a reactive oxygen species scavenger and a neuromodulator. Here we investigate the protective effect of vitamin C on the cerebral cortex neurons of the rat offspring exposed by prenatal noise. Twenty-four rat offspring age 0 from 32 pregnant Wistarmothers were divided into 4 groups equally: K1 (distilled water), K2 (vitamin C), P1 (distilled water + noise), P2 (vitamin C + noise). Vitamin C was administered orally 150 mg/kg of body weight, once daily from day 1 of pregnancy until delivery. Prenatal noise exposure was a white noise given 4 hours daily at 95 dB (from day 15 to delivery). The number of neurons from both hemispheres was counted in duplicate from slides stained with hematoxylin-eosin; 4 ì in thickness, parasagittal sliced, 400x of magnification under a light microscope. Data from 4 groups were then analysed using ANOVA and LSD post-test with significance level of p<0.05. The neuron number of P1 is significantly lower compared to the control groups (p=0.006). When compared to P1, the number of the neurons in P2 is significantly higher (p=0.006). From the current study, vitamin C may protect the cerebral cortex from the adverse effect of prenatal noise during pregnancy in rats.